Manajemen De-eskalasi Cairan pada Syok Hemoragik Obstetri dengan Edema Paru dan Gagal Napas Akut (Laporan Kasus) - Faundra Arieza (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Background: The management of hemorrhagic shock in obstetrics typically involves aggressive fluid resuscitation, often leading to iatrogenic fluid overload and pulmonary edema. Implementing a timely fluid de-escalation (deresuscitation) strategy is critical to facilitate ventilator weaning and achieve early extubation. Case Illustration: A 31-year-old female (G5P3A1) was admitted to the ICU following emergency Re-Cesarean Section due to Grade IV hemorrhagic shock caused by postpartum hemorrhage (PPH) and placenta previa totalis. Intraoperative aggressive resuscitation triggered iatrogenic fluid overload, manifesting as bilateral pulmonary edema and severe gas exchange impairment (initial AaDO2 of 459 mmHg and lactate level of 2.8 mmol/L). Management and Results: Following initial hemodynamic stabilization, an active fluid de-escalation strategy was initiated on Post-Operative Day 1 (POD 1) using continuous furosemide infusion at 10 mg/hour targeting a negative fluid balance. The patient achieved a negative fluid balance of -1485 mL within 24 hours, accompanied by a significant increase in urine output (7.8 mL/kg/hour). This approach successfully reduced the AaDO2 to 162 mmHg and improved lactate clearance to 1.8 mmol/L without compromising hemodynamic stability. The patient was successfully extubated within 18 hours of ICU admission. Conclusion: Early transition from resuscitation to fluid de-escalation, guided by perfusion targets (lactate) and oxygenation markers (AaDO2), is safe in critical obstetric cases. This strategy effectively resolves pulmonary edema and accelerates early extubation.